Simple and functional direct methanol fuel cell stack designs for application in portable and auxiliary power units. (27th July 2016) - Barbera, O.; Stassi, A.; Sebastian, D.; Bonde, J.L.; Giacoppo, G.; D'Urso, C.; Baglio, V.; Aricò, A.S.
Abstract: Simple and functional stack designs were developed for direct methanol fuel cells (DMFCs) with the aim of reducing capital costs. A simplified planar and monopolar ministack, with a reduced number of components, was designed for portable applications. This planar design facilitated the manufacturing of a compact passive mode operation ministack. The ministack provided an output power of 1.30 W under air breathing mode operation, at room pressure and temperature without any auxiliary. For application in auxiliary power units (APU), a self-heating and modular bipolar stack, operating up to 90 °C without internal cooling, was designed. Bipolar stacks consisted of 5–10 cells (100 cm 2 active area), providing an output power of 90–180 W. The recirculated methanol solution was used as thermostating fluid. The stacks achieved a normalised power density per cell of 180 mW cm −2 . Whereas, for the passive mode operation, ministack approached 30 mW cm −2 with 5 M methanol feed. These results favourably compare with the best performance reported in the literature for DMFCs operating under similar conditions. Highlights: Simple and functional DMFC stack designs were developed to reduce capital costs. A simplified and modular bipolar DMFC stack design for assisted power units was developed. Bipolar configuration DMFC stacks achieved a normalised power density of 180 mWcm −2 . A novel design for a passive mode operation DMFC ministack was developed. Performance of 30 mWcm −2 and >75% fuel utilisation was achieved under passive mode.